PATIENT PROFILES AND CLINICAL OUTCOMES IN EMERGENCY DEPARTMENT PRESENTATIONS OF LOWER GASTROINTESTINAL HEMORRHAGE: A RETROSPECTIVE STUDY - TABUR, Ayhan; BÜLBÜL, Emre (Göbeklitepe Medical Science Journal, 2026)
Lower gastrointestinal (GI) bleeding is a significant cause of emergency department (ED) visits and hospital admissions, particularly among older adults. While most cases resolve spontaneously, a subset of patients requires intensive monitoring, interventional treatment, and prolonged hospitalization. This retrospective study analyzed 319 patients presenting with acute lower GI bleeding to the ED of a tertiary care hospital between February 2023 and February 2025. Patients were stratified into WHO/UN-aligned age groups (18–24, 25–44, 45–59, 60–74, 75–89, and ≥90 years). Demographics, presenting symptoms, laboratory findings, length of hospital stay (LOS), and in-hospital mortality were evaluated. Results showed a median age of 61 years (IQR 49–74), with 56.4% being male. Hematochezia was the most frequent presenting symptom across all age groups. LOS significantly increased with advancing age (Kruskal–Wallis H=44.27, df=5, p<0.0001; Spearman ρ=0.30, p<0.0001), but no significant sex-related differences were observed (Mann–Whitney p=0.73). Male–female comparisons within age groups did not reach significance after Holm correction. In-hospital mortality occurred in 1.6% of patients (n=5), all aged ≥60 years. In conclusion, lower GI bleeding was most prevalent in middle-aged and older adults, with hospital LOS strongly associated with age but not with sex. These findings highlight the importance of age-specific risk assessment and tailored management strategies for ED presentations of lower GI bleeding.